2021
DOI: 10.1108/jaee-01-2020-0013
|View full text |Cite
|
Sign up to set email alerts
|

Fair value accounting implementation challenges in South Africa

Abstract: PurposeThe objective of this research is to explore the challenges being encountered when applying and implementing fair value accounting requirements, focusing specifically on the determination of fair value per International Financial Reporting Standards (IFRS) 13: Fair value measurement (IFRS 13) in the South African capital market.Design/methodology/approachData are collected from 20 detailed interviews, primarily with preparers and interpretively analysed to identify how individuals internalise the requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 84 publications
(227 reference statements)
0
10
0
Order By: Relevance
“…On the other hand, opponents argue that fair values are subject to greater estimation error by management, and prone to greater managerial discretion. In particular, the reliability concept suffers fundamental problems if fair values are not readily observed on the active markets and management must estimate these using considerable discretion or manipulation (Landsman, 2007;Pandya et al, 2021). The research suggest that fair values are informative to investors, but the value relevance diminishes with higher level of fair value hierarchy, which is often a subject of management bias and measurement error (Song et al, 2010).…”
Section: Domain 1: Fva -A Results Of a Conceptual Shift In Financial Reportingmentioning
confidence: 96%
See 1 more Smart Citation
“…On the other hand, opponents argue that fair values are subject to greater estimation error by management, and prone to greater managerial discretion. In particular, the reliability concept suffers fundamental problems if fair values are not readily observed on the active markets and management must estimate these using considerable discretion or manipulation (Landsman, 2007;Pandya et al, 2021). The research suggest that fair values are informative to investors, but the value relevance diminishes with higher level of fair value hierarchy, which is often a subject of management bias and measurement error (Song et al, 2010).…”
Section: Domain 1: Fva -A Results Of a Conceptual Shift In Financial Reportingmentioning
confidence: 96%
“…Despite the concerns over fair value fictionality and intellectual incoherence, the proponents frequently argue that it offers a higher and updated level of information to financial statement users supporting its primacy in current standard setters" viewpoint (Danbolt andRees, 2008, Whittington, 2008). Since FVA is based on the philosophical underpinnings of "Western" market economies, its application in cultures where market inefficiencies and relational contracting are present may not be suitable (Pandya et al, 2021;Balfoort et al, 2017;He at al., 2012;Peng and Bewley, 2010). Balfoort et al (2017) argue that the qualitative characteristics of neutrality and faithful representation in fair value measurement may seriously be undermined in Asian economics and transactions.…”
Section: Domain 1: Fva -A Results Of a Conceptual Shift In Financial Reportingmentioning
confidence: 99%
“…As for (Nordlund, 2021) it indicated that the International Valuation Standards Committee (IVSC) defined the fair value in the third criterion for valuing assets for the purposes of preparing financial statements and related accounts as "an estimated amount in exchange for an asset exchange on the valuation date between a buyer and seller, and both are willing to conclude a deal in the light of a neutral market, as each of them has sufficient information and has complete freedom and without coercion to complete the deal. However, (Pandya, 2021) indicates that the Accounting Standards Committee in England and Wales has defined the fair value of assets as "the price at which the asset can be sold in free transactions away from the parties involved in the buying and selling process." Furthermore, in Iraq, Accounting and Regulatory Standards Board (2001) defined the fair value within accounting rule no.…”
Section: -Theoretical Framework For Research / Fair Value 31 the Conc...mentioning
confidence: 99%
“…However, With the end of the twentieth century and the world's tendency towards the new world order (globalization), the emergence of major multinational companies and the economic openness between countries, and the interconnection of their economies with each other, especially in the areas of global trade and freedom of commercial and financial dealings, all of this led to pressures on the accounting profession and affecting some of the principles on which it is based, including the historical cost principle, which is facing severe criticism in the direction of the transition to the application of fair value (Nordlund, 2021). And (Pandya, 2021) indicates that as a result of these pressures, the trend towards applying fair value accounting as a basic requirement in proving the treatment of financial events and operations began to be more accurate and closer to the actual reality in accordance with the prevailing conditions in order to achieve the efficiency and reliability of the published financial statements, which prompted the specialized professional bodies to issue Accounting standards that meet the continuing needs that coincide with the great development on the international financial level, especially with regard to the application of fair value. (He et al, 2018) confirms that many specialized professional bodies issued the foundations that require recognition of some changes that occur in financial instruments and the impact of many Items with those changes such as items (income statement, change in shareholders' equity and cash flow (including the Financial Accounting Standards Board and the International Accounting Standards Board).…”
Section: -Introductionmentioning
confidence: 99%
“…However, where Level 1 fair values are not available, management must estimate the fair value. In these cases, assets are 'markedto-model' (not market) and their measurement is more subjective and open to estimation error (Haswell and Evans 2018;Pandya et al 2021).…”
Section: The Historical Cost and Fair Value Knowledge Templatesmentioning
confidence: 99%